(untitled) - The United Nations Development Programme (UNDP) (New York, 2010)
The 20th Anniversary edition is a time to take stock, reflect and move forward. It rigorously reviews the past two decades of human development trends and challenges, and provides newly available data and supplementary indices weighing the effect of income inequalities, gender disparities and household-level poverty.
Keywords: Environmental economics,Kinh tế môi trường,Thay đổi xã hội,Social change